METODE ROYAL ACADEMY OF DANCE (RAD) PADA PEMBELAJARAN TARI PRE BALLET MARLUPI DANCE ACADEMY - Melia Cahya Agusti Sidik; Dwi Junianti Lestari; Dadang Dwi Septiyan (Boting Langi: Jurnal Seni Pertunjukan, 2025)
This study aims to examine the application of the Royal Academy of Dance (RAD) method in learning pre ballet dance at Marlupi Dance Academy (MDA) as an effort to develop character, creativity, and motor skills in early childhood. Marlupi Dance Academy is a dance education institution that has been established since 1956 and consistently applies the RAD method as an international approach in its curriculum. The RAD method, which originated in the UK, is designed to provide a systematic, progressive, and developmentally appropriate structure for ballet learning. The research approach used was qualitative with descriptive methods, through direct observation, semi-structured interviews with trainers, students, and parents, as well as documentation in the form of photos and videos. The results show that the RAD method is applied through several stages of learning, including the provision of basic movement materials, introduction to music and expression, as well as the development of creativity and imagination. The learning process is conducted in three age-based pre ballet class categories, namely Pre School (2.5-4 years old), Pre Primary (5 years old and above), and Primary. Each category is designed to foster motor skills, musicality, and body awareness through a fun, educational, and interactive approach. The factors that influence the implementation of this method are divided into two, namely internal and external factors. Internal factors include student motivation and interest, self-confidence, physical and motor condition, as well as discipline and consistency. Meanwhile, external factors include the role of RAD-certified trainers, the quality of learning facilities and media, developmentally appropriate teaching methods, a positive learning environment, and parental support. The integration of both factors supports the effectiveness of learning, and contributes to children's character building, discipline and creativity from an early age